Learning motivation tendencies among preschoolers: Impact of executive functions and gender differences - Aleksander Veraksa; Margarita Gavrilova; Janne Lepola (Acta Psychologica, 2022)
The current study aimed to validate the Russian version of the Child Behaviour Motivation Scale (CBeMO), examine gender differences in motivational tendencies, and explore the impact of executive functions on learning motivation tendencies among children. The sample consisted of 434 typically developing 5–6 years old children. The confirmatory factor analysis showed that according to the evaluation criteria, the model is poorly fitted to the data. However, internal consistency analysis confirmed acceptable levels of reliability and unidimensionality of the CBeMO scales. The identified internal structure of CBeMO indicates an overlap between CBeMO items related to task avoidance and social dependence on the Russian sample. The study revealed differences between girls and boys in all three CBeMO scales. Concerning executive functioning, it was revealed that motor persistence skills and working memory have an impact on the learning motivation tendencies among children, when controlling for group size, age, gender and non-verbal intelligence.